Udejanjanje načel trajnostnega razvoja v malih, antropogeno preobremenjenih porečjih - Šterbenk, Emil (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2007)
In the mid-eighties of the 20th century waters in the Šalek Valley were heavily polluted. Due to degradation of waters a Water improvement programme was started. Methodology of environmental improvement of Paka watershed could be adjusted and applied also in other similar over-burdened areas.
Keywords: Šalek Valley; Šaleška dolina; hidrogeografija; površinske vode; vodotoki; porečja; onesnaženost; pollution; degradacija okolja; preprečevanje; čistilne naprave; environmental protection; varstvo okolja; sustainable development; trajnostni razvoj; sonaravni razvoj